2019 23rd International Conference Electronics 2019
DOI: 10.1109/electronics.2019.8765577
|View full text |Cite
|
Sign up to set email alerts
|

Bluetooth Low Energy Throughput in Densely Deployed Radio Environment

Abstract: Bluetooth Low Energy (BLE) is a promising 2.4 GHz technology for Body Area Networks (BAN) in healthcare and lifestyle applications. However, the global increase of wireless devices using the crowded spectrum in the 2.4 GHz frequency band can create coexistence issues. This work studies the performance of BLE in environments with multiple BLE devices. An experimental setup consisting of 10 BLE nodes is used to measure BLE application throughput with different connection parameters and under different interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…From the performance evaluation of the system itself, the main bottleneck of the sensor data transmission is the UART connection node between the Bluetooth module and the MCU on the central. The application throughput of the Bluetooth Low Energy is up to 1.4 megabits per second [ 17 ] (for classical Bluetooth, it is even higher) and baudrates of the SPI range up to several megahertz. However, UART baudrates supported by microcontrollers are mostly lower.…”
Section: Experimental Setup Scenario and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the performance evaluation of the system itself, the main bottleneck of the sensor data transmission is the UART connection node between the Bluetooth module and the MCU on the central. The application throughput of the Bluetooth Low Energy is up to 1.4 megabits per second [ 17 ] (for classical Bluetooth, it is even higher) and baudrates of the SPI range up to several megahertz. However, UART baudrates supported by microcontrollers are mostly lower.…”
Section: Experimental Setup Scenario and Resultsmentioning
confidence: 99%
“…The multi-branch SPI daisy-chain configuration allows for synchronized real-time sampling design and centralized power supply for sensor nodes with only four wired connections. Compared to wireless channels, wired connections are less susceptible to environmental interference sources, especially in the crowded 2.4 GHz ISM band [ 17 ]. Wired connections embedded in the clothing can provide power delivery using one centralized power source.…”
Section: Sensor Network Architecturementioning
confidence: 99%
“…The authors suggested that further improving the reliability of BLE is possible by adding some extra techniques, such as Carrier Sense Multiple Access (CSMA). A. Ancans et al [ 20 ] studied the BLE throughput under Wi-Fi interference and other BLE devices. The parameters, such as the BLE connection interval (CI) and PHY mode, which are mainly used to adjust the throughput and communication range, were considered in their work.…”
Section: Related Workmentioning
confidence: 99%
“…A low power, wireless demonstration platform for wearable IoT flexible systems was designed and developed in view of our specific application for health and environment monitoring. The core activity for combining various contributions into unique proof of concept demonstrators is based on previous works [ 10 , 11 , 12 , 13 ].…”
Section: Low-power Wearable Sensing Platform: Architecture Specifmentioning
confidence: 99%
“…This platform support both analog and digital sensors, developed by Convergence project partners, such as activity [ 4 , 11 ], sweat and pH [ 14 ] and gas sensors like NO x [ 15 , 16 ], CO x [ 7 ], NH x compounds.…”
Section: Low-power Wearable Sensing Platform: Architecture Specifmentioning
confidence: 99%